2014
DOI: 10.2466/25.pms.119c26z1
|View full text |Cite
|
Sign up to set email alerts
|

Ballroom Dance and Body Size Perception

Abstract: Ballroom dancing consists in the performance of rhythmic movements guided by music, which provide sensorimotor integration and stimulate feelings. The body schema is the unconscious sensorimotor representation that allows the individual to perceive his anatomical body in space. Comprising tactile, proprioceptive, kinesthetic, and environmental information, it is directly related to movement. The aim of this study was to investigate the influence of non-competitive practice of ballroom dancing on body perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 14 publications
(15 reference statements)
0
28
0
1
Order By: Relevance
“…The studies investigate different populations: Eleven studies investigate children and adolescents (Blackman et al, 1988 ; Roswal et al, 1988 ; Caf et al, 1997 ; Backe and Graefe, 2004 ; Connolly et al, 2011 ; Zitomer and Reid, 2011 ; Romero, 2012 ; Studer-Lüthi and Züger, 2012 ; Jounghwa et al, 2013 ; Jago et al, 2015 ; Duberg et al, 2016 ). Thirteen studies examine an adult sample (Aşçi, 2002 , 2009 ; Baptista et al, 2012 ; Pinniger et al, 2012 , 2013a , b , c ; Thornberg et al, 2012 ; Fonseca et al, 2014 ; Soares Costa de Mendonça et al, 2015 ; Stickley et al, 2015 ; Mandelbaum et al, 2016 ; Kosmat and Vranic, 2017 ). Eleven studies investigate a population with physical or mental disorders (Roswal et al, 1988 ; Caf et al, 1997 ; Backe and Graefe, 2004 ; Zitomer and Reid, 2011 ; Baptista et al, 2012 ; Pinniger et al, 2012 , 2013a , b , c ; Duberg et al, 2016 ; Mandelbaum et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies investigate different populations: Eleven studies investigate children and adolescents (Blackman et al, 1988 ; Roswal et al, 1988 ; Caf et al, 1997 ; Backe and Graefe, 2004 ; Connolly et al, 2011 ; Zitomer and Reid, 2011 ; Romero, 2012 ; Studer-Lüthi and Züger, 2012 ; Jounghwa et al, 2013 ; Jago et al, 2015 ; Duberg et al, 2016 ). Thirteen studies examine an adult sample (Aşçi, 2002 , 2009 ; Baptista et al, 2012 ; Pinniger et al, 2012 , 2013a , b , c ; Thornberg et al, 2012 ; Fonseca et al, 2014 ; Soares Costa de Mendonça et al, 2015 ; Stickley et al, 2015 ; Mandelbaum et al, 2016 ; Kosmat and Vranic, 2017 ). Eleven studies investigate a population with physical or mental disorders (Roswal et al, 1988 ; Caf et al, 1997 ; Backe and Graefe, 2004 ; Zitomer and Reid, 2011 ; Baptista et al, 2012 ; Pinniger et al, 2012 , 2013a , b , c ; Duberg et al, 2016 ; Mandelbaum et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigate a population with special disorders (Baptista et al, 2012 ; Pinniger et al, 2012 , 2013a , b , c ; Mandelbaum et al, 2016 ). Six studies investigate a sample ranging from 8 to 41 participants (Thornberg et al, 2012 ; Pinniger et al, 2013a , c ; Fonseca et al, 2014 ; Mandelbaum et al, 2016 ; Kosmat and Vranic, 2017 ). Four studies show a sample size of 64 up to 89 participants (Baptista et al, 2012 ; Pinniger et al, 2012 , 2013b ; Soares Costa de Mendonça et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Minton (2003) reported that students who received dancing classes had more abstract and creative thinking skills compared to those who did not receive dancing courses. Fonseca et al (2014) observed that ballroom dancing brought perceptual benefits for those who practiced it. Krampe (2013) found that dance-based therapy was mildly or moderately effective in several components of balance and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Damasio, (2010) stated that with every move, new cortical maps are created to increase the repertoire of new possible motor responses. Messages obtained by the "sensory gateway" i.e., sensory organs during body movements, are organized in an overall brain map and are shaped according to changes during development, as well as variations in the amplitude and quality of movements [2].…”
Section: Specific Coordination Abilitiesmentioning
confidence: 99%